Combination of drug-eluting bead transarterial chemoembolization and PD-1 inhibitor for treatment of unresectable head and neck squamous cell carcinoma: an initial, short-term clinical experience in a single-center retrospective cohort study - Sun, Bo; Gao, Jin Qi; Li, Ruo Jie; Song, Lei; Li, Na; Gao, Fei (Frontiers in Immunology, 2025)
IntroductionThis study investigated the clinical efficacy and safety of CalliSpheres® drug-eluting bead transarterial chemoembolization (DEB-TACE) combined with programmed death protein (PD)-1 inhibitors for treatment of unresectable head and neck squamous cell carcinoma (HNSCC).MethodsClinical data of 31 patients with unresectable HNSCC were retrospectively analyzed. All patients received local treatment with DEB-TACE combined with systemic PD-1 inhibitor. Modified Response Evaluation Criteria in Solid Tumors (mRECIST) criteria were used to evaluate the tumor response at 1, 3 and 6 months after the first treatment. Progression-free survival and overall survival were recorded. The changes in quality of life before and after treatment and adverse reactions during treatment were recorded.ResultsPatients were treated with DEB-TACE 51 (average 1.65 ± 0.51) times. At 1, 3 and 6 months after the first treatment, objective response rate was 96.77%, 87.09% and 74.19%, and disease control rate was 100%, 96.77% and 83.87%, respectively. As of October 31, 2024, the mean follow-up was 21.71 ± 9.56 months, median survival time was 9.0 months, and the median progression-free survival was 19.0 months. The adverse reactions related to DEB-TACE were mainly fever, pain, nausea and vomiting; all of which were mild and relieved after symptomatic treatment. Three patients had mild skin ulceration in the embolic area, which healed after symptomatic treatment, and no serious complications such as ectopic embolism occurred. The adverse reactions associated with PD-1 inhibitor treatment were mainly fatigue, hypothyroidism and rash. Most of these were grade 1/2, three patients had grade 3 adverse reactions, but no grade 4 adverse reactions occurred. One month after the first treatment, the scores of physical function, emotional function and general health status increased, and the scores of pain, insomnia and anorexia decreased, and quality of life was significantly improved.DiscussionCombination of DEB-TACE with PD-1 inhibitors is safe and effective for treatment of unresectable HNSCC, significantly improves quality of life, and warrants clinical promotion and application.